Fracturing fluid thickening agent amphoteric polyacrylamide and preparation method thereof
Through a multi-step polymerization method, calcium ions and iron ions are introduced to form amphoteric polyacrylamides with high viscosity and good salt resistance, which solves the problem of low salt resistance and viscosity of polyacrylamides in the prior art.
Patent Information
- Application Number
- CN202411775826.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-22
AI Technical Summary
In the existing polyacrylamide synthesis methods, the anionic polyacrylamide has poor salt resistance, while the cationic polyacrylamide has low water-soluble and viscosity, so it is difficult for zwitterionic copolymers to improve their salt resistance while improving their viscosity.
A preparation method is adopted to generate homopolymers through primary polymerization, and anionic and cationic monomers, calcium ions and iron ions are introduced in the secondary polymerization, and polymer colloids are formed by ultraviolet light irradiation, and finally a fracturing liquid thickening agent amphoteric polyacrylamide is obtained through granulation, drying, crushing and sieving.
The salt resistance and viscosity of amphoteric polyacrylamide is improved, and the electrostatic attraction of the polymer chain is enhanced through ion-polymer interaction, thereby enhancing the viscosity of the product.
Smart Images

Figure CN119859222A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyacrylamide synthesis, in particular to an amphoteric polyacrylamide as a fracturing fluid thickener and a preparation method thereof. Background Art
[0002] Polymer fracturing fluid usually uses anionic polyacrylamide as a thickener. Anionic polyacrylamide has a certain viscosity-increasing effect, but its salt resistance is poor. Although cationic polyacrylamide has greatly improved the salt resistance of polyacrylamide, it still has problems such as water solubility and low viscosity. Therefore, zwitterionic copolymers have become a better choice.
[0003] There are two existing methods for synthesizing polyacrylamide. One is to select anionic monomers, cationic monomers and acrylamide nonionic monomers to synthesize terpolymers through polymerization. The advantage of this method is that the cationic and anionic degrees of the polymers are accurately controlled, and products with higher cationic degrees can be synthesized, but the selection of monomer reactivity requires high requirements, otherwise it is difficult to prepare products with higher relative molecular mass. The other is to directly select polyacrylamide or partially hydrolyzed polyacrylamide products for cationic improvement, such as introducing cationic groups on acrylamide units through Mannich reaction. The advantage of this method is that the preparation process is simple and the cost is low, but the amphoteric polyacrylamide prepared by this method has low viscosity.
[0004] To this end, in view of the defects of the second synthesis method mentioned in the above background technology, the present invention proposes an amphoteric polyacrylamide as a fracturing fluid thickener and a preparation method thereof. Summary of the invention
[0005] The object of the present invention is to provide a fracturing fluid thickener amphoteric polyacrylamide and a preparation method thereof to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing amphoteric polyacrylamide as a fracturing fluid thickener comprises the following steps: S1. Primary polymerization: Add acrylamide monomer to deionized water, heat to 30°C until the acrylamide monomer is completely dissolved, then continue to add initiator and sodium bicarbonate to obtain a mixed solution, continue to heat the mixed solution to 70-90°C and react for 4-7h to obtain a homopolymer; S2, cooling the homopolymer obtained in step S1 to room temperature for 1-2 hours, adding deionized water, and adding 10% by mass sodium hydroxide solution to adjust the pH to 6.8-7.2, then adding octylphenol polyoxyethylene ether and sodium lauryl sulfate, stirring for 1-3 hours, and then continuing to add calcium chloride and ferric chloride, stirring for 0.5-1 hour to obtain a mixture; S3, secondary polymerization: the mixture obtained in step S2 is further cooled to 4-6°C, and anionic monomers, cationic monomers, complexing agents, chain transfer agents, chaotropic agents and composite initiators are continuously added, and a polymer colloid is obtained by irradiating the mixture with ultraviolet light having a wavelength of 360-380 nm for 1-2 hours; S4, granulating, drying, crushing and sieving the polymer colloid obtained in step S3 to obtain amphoteric polyacrylamide as a thickening agent for fracturing fluid.
[0007] Furthermore, the initiator in step S1 is ammonium persulfate, and the mass ratio of the initiator, sodium bicarbonate, acrylamide monomer and deionized water in step S1 is 1:(1-3):(10-16):(18-40).
[0008] Furthermore, the mass ratio of the deionized water added in step S1 to the deionized water added in step S2 is 1:(1-1.4), the mass ratio of calcium chloride, ferric chloride, octylphenol polyoxyethylene ether and sodium dodecyl sulfate is 1:(0.6-2.1):(200-800):(600-1200), and the mass ratio of octylphenol polyoxyethylene ether to acrylamide monomer is 1:(80-140).
[0009] Furthermore, in step S3, the anionic monomer is 2-acrylammonium-2-methylpropanesulfonic acid, the cationic monomer is acryloyloxyethyltrimethylammonium chloride or methacryloyloxyethyltrimethylammonium chloride, and the composite initiator is a mixture of persulfate, sulfite and azo compound; and the mass ratio of the composite initiator, cationic monomer, anionic monomer in step S3 to the acrylamide monomer in step S1 is 1:(4-6):(8-20):(8-20).
[0010] Furthermore, the persulfate is selected from one of ammonium persulfate, potassium persulfate, and sodium persulfate; the sulfite is selected from one of sodium sulfite, potassium sulfite, sodium bisulfite, and potassium bisulfite; and the azo compound is selected from one of azobisisobutyronitrile, dimethyl azobisisobutyrate, and azobisisobutylamidine hydrochloride.
[0011] Furthermore, the mass ratio of the persulfate, the sulfite and the azo compound is 1:1:(0.6-2.4).
[0012] Furthermore, the complexing agent is one of 2,2-bipyridine, sodium ethylenediaminetetramethylenephosphate or tris(2-dimethylamino)ethylamine, the chain transfer agent is one of isopropanol, isobutanol or pentaerythritol, the solubilizing agent is one of urea or thiourea, and the mass ratio of the complexing agent, chain transfer agent, solubilizing agent and acrylamide monomer is 1:(2-5):(10-20):(5000-11000).
[0013] Furthermore, nitrogen gas was introduced into the reaction system of the primary polymerization in step S1 and the secondary polymerization in step S3, and the nitrogen gas had a purity of 99.99% and a flow rate of 60 m / s. 3 / h.
[0014] A fracturing fluid thickener amphoteric polyacrylamide is prepared by the above-mentioned preparation method of the fracturing fluid thickener amphoteric polyacrylamide.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The polyacrylamide prepared by the present invention can improve the salt tolerance of the product and effectively improve the viscosity of the product through the co-polymerization of anions and cations. During the preparation process, calcium ions and iron ions are introduced to enhance the interaction between polymer chains. This ion-polymer interaction generates stronger electrostatic attraction between polymer chains, thereby increasing the viscosity of the polymer; 2. The amphoteric polyacrylamide prepared by the present invention adopts the steps of synthesizing a homopolymer first and then synthesizing a copolymer. In the process of forming the homopolymer, due to the introduction of sodium bicarbonate, more pores are generated in the gel produced by the homopolymer finally formed, which are used for the attachment of ions, so that the anion and cation distribution of the overall prepared terpolymer is more reasonable, thereby improving the product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The present invention is a process flow chart for preparing amphoteric polyacrylamide. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] See also Figure 1 , the present invention provides a technical solution: Example 1 A method for preparing amphoteric polyacrylamide as a fracturing fluid thickener, characterized in that it comprises the following steps: S1. Primary polymerization: 25.48 g of acrylamide monomer was added to 50.96 g of deionized water, and heated to 30° C. until the acrylamide monomer was completely dissolved, and then 1.82 g of ammonium persulfate and 3.48 g of sodium bicarbonate were added to obtain a mixed solution, and the mixed solution was further heated to 75° C. and reacted for 6 h to obtain a homopolymer; S2, the homopolymer obtained in step S1 was cooled to room temperature and placed for 1.6 hours, 61.15g of deionized water was added, and a 10% sodium hydroxide solution was added to adjust the pH to 7.1, followed by adding 0.42g of octylphenol polyoxyethylene ether and 0.56g of sodium dodecyl sulfate, stirring for 1.6 hours, and then continuing to add 0.7mg of calcium chloride and 1.2mg of ferric chloride, stirring for 0.8h to obtain a mixture; S3, secondary polymerization: the mixture obtained in step S2 is further cooled to 5°C, and 25.42g of 2-acrylammonium-2-methylpropanesulfonic acid, 7.96g of acryloyloxyethyltrimethylammonium chloride, 3.18mg of sodium ethylenediaminetetramethylenephosphate, 12.72mg of isobutyl alcohol, 47.7mg of urea, 0.53g of ammonium persulfate, 0.53g of sodium sulfite and 0.53g of azobisisobutyronitrile are added, and the mixture is irradiated with ultraviolet light of a wavelength of 370nm for 1.5h to obtain a polymer colloid; S4, granulating, drying, crushing and sieving the polymer colloid obtained in step S3 to obtain amphoteric polyacrylamide as a thickening agent for fracturing fluid.
[0019] Example 2 A method for preparing amphoteric polyacrylamide as a fracturing fluid thickener, characterized in that it comprises the following steps: S1. Primary polymerization: 15.8 g of acrylamide monomer was added to 28.44 g of deionized water, and heated to 30° C. until the acrylamide monomer was completely dissolved, and then 1.58 g of ammonium persulfate and 1.58 g of sodium bicarbonate were added to obtain a mixed solution, and the mixed solution was further heated to 70° C. and reacted for 4 hours to obtain a homopolymer; S2, the homopolymer obtained in step S1 was cooled to room temperature and placed for 1 hour, 28.44g of deionized water was added, and a 10% sodium hydroxide solution was added to adjust the pH to 6.8, followed by adding 0.19g of octylphenol polyoxyethylene ether and 0.58g of sodium dodecyl sulfate, stirring for 1 hour, and then continuing to add 0.98mg of calcium chloride and 0.59mg of ferric chloride, stirring for 0.5h to obtain a mixture; S3, secondary polymerization: the mixture obtained in step S2 is further cooled to 4°C, and 15.8 g of 2-acrylammonium-2-methylpropanesulfonic acid, 7.9 g of acryloyloxyethyltrimethylammonium chloride, 3.16 mg of tris(2-dimethylamino)ethylamine, 6.32 mg of isopropanol, 31.6 mg of urea, 0.76 g of ammonium persulfate, 0.76 g of sodium sulfite and 0.45 g of dimethyl azobisisobutyrate are added, and the mixture is irradiated with ultraviolet light of a wavelength of 360 nm for 1 h to obtain a polymer colloid; S4, granulating, drying, crushing and sieving the polymer colloid obtained in step S3 to obtain amphoteric polyacrylamide as a thickening agent for fracturing fluid.
[0020] Example 3 A method for preparing amphoteric polyacrylamide as a fracturing fluid thickener, characterized in that it comprises the following steps: S1. Primary polymerization: 39.36 g of acrylamide monomer was added to 98.4 g of deionized water, and heated to 30° C. until the acrylamide monomer was completely dissolved. Then, 2.46 g of ammonium persulfate and 7.38 g of sodium bicarbonate were added to obtain a mixed solution. The mixed solution was further heated to 70° C. and reacted for 4 h to obtain a homopolymer. S2, the homopolymer obtained in step S1 was cooled to room temperature and placed for 2 hours, 137.76g of deionized water was added, and a 10% sodium hydroxide solution was added to adjust the pH to 7.2, followed by adding 0.28g of octylphenol polyoxyethylene ether and 0.42g of sodium dodecyl sulfate, stirring for 3 hours, and then continuing to add 0.35mg of calcium chloride and 0.7mg of ferric chloride, stirring for 1 hour to obtain a mixture; S3, secondary polymerization: the mixture obtained in step S2 is further cooled to 6°C, and 39.36 g of 2-acrylammonium-2-methylpropanesulfonic acid, 11.8 g of methacryloyloxyethyltrimethylammonium chloride, 3.57 mg of tris(2-dimethylamino)ethylamine, 17.85 mg of isopropanol, 71.4 mg of urea, 0.45 g of ammonium persulfate, 0.45 g of sodium sulfite and 1.09 g of dimethyl azobisisobutyrate are added, and the mixture is irradiated with ultraviolet light of a wavelength of 380 nm for 2 h to obtain a polymer colloid; S4, granulating, drying, crushing and sieving the polymer colloid obtained in step S3 to obtain amphoteric polyacrylamide as a thickening agent for fracturing fluid.
[0021] Example 4 A method for preparing amphoteric polyacrylamide as a fracturing fluid thickener, characterized in that it comprises the following steps: S1. Primary polymerization: 22.2 g of acrylamide monomer was added to 51.8 g of deionized water, and heated to 30° C. until the acrylamide monomer was completely dissolved. Then, 1.48 g of ammonium persulfate and 2.96 g of sodium bicarbonate were added to obtain a mixed solution. The mixed solution was further heated to 80° C. and reacted for 5.5 h to obtain a homopolymer. S2, the homopolymer obtained in step S1 was cooled to room temperature and placed for 2 hours, 56.9 g of deionized water was added, and a 10% sodium hydroxide solution was added to adjust the pH to 7.0, followed by adding 0.21 g of octylphenol polyoxyethylene ether and 0.56 g of sodium dodecyl sulfate, stirring for 1.6 hours, and then continuing to add 0.36 mg of calcium chloride and 0.66 mg of ferric chloride, stirring for 1 hour to obtain a mixture; S3, secondary polymerization: the mixture obtained in step S2 is further cooled to 5°C, and 20.7g of 2-acrylammonium-2-methylpropanesulfonic acid, 6.9g of acryloyloxyethyltrimethylammonium chloride, 2.4mg of sodium ethylenediaminetetramethylenephosphate, 5.1mg of isobutyl alcohol, 25.6mg of urea, 0.46g of ammonium persulfate, 0.46g of sodium sulfite and 0.46g of dimethyl azobisisobutyrate are added, and the mixture is irradiated with ultraviolet light of a wavelength of 360nm for 1.2h to obtain a polymer colloid; S4, granulating, drying, crushing and sieving the polymer colloid obtained in step S3 to obtain amphoteric polyacrylamide as a thickening agent for fracturing fluid.
[0022] Nitrogen was introduced into the reaction system of the primary polymerization in step S1 of the above embodiment 1-4 and the secondary polymerization in step S3. The nitrogen purity was 99.99% and the flow rate was 60m / s. 3 / h.
[0023] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step S1 is omitted, thereby eliminating the addition of sodium bicarbonate, and the other steps are exactly the same as those in Example 1.
[0024] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step S2 is omitted, thereby eliminating the addition of calcium chloride and ferric chloride, and the remaining steps are exactly the same as those in Example 1.
[0025] Comparative Example 3 Compared with Comparative Example 1, Comparative Example 3 eliminates the addition of calcium chloride and ferric chloride, and the remaining steps are exactly the same as those of Comparative Example 1.
[0026] A total of 7 groups of amphoteric polyacrylamide were prepared through the above Examples 1-4 and Comparative Examples 1-3, and sodium chloride solutions with a mineralization degree of 0-20 g / L and calcium chloride solutions with a mineralization degree of 0-10 g / L were prepared respectively. 0.5% of the amphoteric polyacrylamide of Examples 1-4 and Comparative Examples 1-3 were added to the sodium chloride solutions and calcium chloride solutions with different mineralization degrees, respectively, and stirred evenly. Then, the apparent viscosity thereof was tested using a six-speed rotary viscometer at a temperature of 30° C. The results are shown in Table 1 below: Table 1: Apparent viscosity of amphoteric polyacrylamides prepared in Examples 1-4 and Comparative Examples 1-3 in sodium chloride solutions with different mineralization degrees / mPa·s It can be seen from the data in Table 1 above that the present invention can improve the viscosity of the prepared amphoteric polyacrylamide by the reasonable introduction of calcium ions and iron ions. At the same time, in the process of preparing the homopolymer, since the homopolymer can form a porous colloidal substance, it is convenient to introduce ions, thereby further improving the viscosity of the finished product.
[0027] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing amphoteric polyacrylamide as a fracturing fluid thickener, characterized in that: The steps include: S1. Primary polymerization: Add acrylamide monomer to deionized water, heat to 30°C until the acrylamide monomer is completely dissolved, then continue to add initiator and sodium bicarbonate to obtain a mixed solution, continue to heat the mixed solution to 70-90°C and react for 4-7h to obtain a homopolymer; S2, cooling the homopolymer obtained in step S1 to room temperature for 1-2 hours, adding deionized water, and adding 10% by mass sodium hydroxide solution to adjust the pH to 6.8-7.2, then adding octylphenol polyoxyethylene ether and sodium dodecyl sulfate, stirring for 1-3 hours, and then continuing to add calcium chloride and ferric chloride, stirring for 0.5-1 hour to obtain a mixture; S3, secondary polymerization: the mixture obtained in step S2 is further cooled to 4-6°C, and anionic monomers, cationic monomers, complexing agents, chain transfer agents, chaotropic agents and composite initiators are continuously added, and a polymer colloid is obtained by irradiating the mixture with ultraviolet light having a wavelength of 360-380 nm for 1-2 hours; S4, granulating, drying, crushing and sieving the polymer colloid obtained in step S3 to obtain amphoteric polyacrylamide as a thickening agent for fracturing fluid.
2. The method for preparing amphoteric polyacrylamide as a thickening agent for fracturing fluid according to claim 1, characterized in that: The initiator in step S1 is ammonium persulfate, and the mass ratio of the initiator, sodium bicarbonate, acrylamide monomer and deionized water in step S1 is 1:(1-3):(10-16):(18-40).
3. The method for preparing amphoteric polyacrylamide as a thickening agent for fracturing fluid according to claim 1, characterized in that: The mass ratio of the deionized water added in step S1 to the deionized water added in step S2 is 1:(1-1.4), the mass ratio of calcium chloride, ferric chloride, octylphenol polyoxyethylene ether and sodium lauryl sulfate is 1:(0.6-2.1):(200-800):(600-1200), and the mass ratio of octylphenol polyoxyethylene ether to acrylamide monomer is 1:(80-140).
4. The method for preparing amphoteric polyacrylamide as a thickening agent for fracturing fluid according to claim 1, characterized in that: In step S3, the anionic monomer is 2-acrylammonium-2-methylpropanesulfonic acid, the cationic monomer is acryloyloxyethyltrimethylammonium chloride or methacryloyloxyethyltrimethylammonium chloride, and the composite initiator is a mixture of persulfate, sulfite and azo compound; the mass ratio of the composite initiator, cationic monomer, anionic monomer in step S3 to the acrylamide monomer in step S1 is 1:(4-6):(8-20):(8-20).
5. The method for preparing amphoteric polyacrylamide as a thickening agent for fracturing fluid according to claim 4, characterized in that: The persulfate is selected from one of ammonium persulfate, potassium persulfate, and sodium persulfate; the sulfite is selected from one of sodium sulfite, potassium sulfite, sodium bisulfite, and potassium bisulfite; the azo compound is selected from one of azobisisobutyronitrile, dimethyl azobisisobutyrate, and azobisisobutylamidine hydrochloride.
6. The method for preparing amphoteric polyacrylamide as a thickening agent for fracturing fluid according to claim 4, characterized in that: The mass ratio of the persulfate, the sulfite and the azo compound is 1:1:(0.6-2.4).
7. The method for preparing amphoteric polyacrylamide as a thickening agent for fracturing fluid according to claim 1, characterized in that: The complexing agent is one of 2,2-bipyridine, sodium ethylenediaminetetramethylenephosphate or tris(2-dimethylamino)ethylamine, the chain transfer agent is one of isopropanol, isobutanol or pentaerythritol, the solubilizing agent is one of urea or thiourea, and the mass ratio of the complexing agent, the chain transfer agent, the solubilizing agent and the acrylamide monomer is 1:(2-5):(10-20):(5000-11000).
8. The method for preparing amphoteric polyacrylamide as a thickening agent for fracturing fluid according to claim 1, characterized in that: Nitrogen was introduced into the reaction system of the primary polymerization in step S1 and the secondary polymerization in step S3, and the nitrogen purity was 99.99% and the flow rate was 60m / s. 3 / h.
9. A fracturing fluid thickener amphoteric polyacrylamide, characterized in that: The method is prepared by the method for preparing amphoteric polyacrylamide as a fracturing fluid thickener according to any one of claims 1 to 8.
Citation Information
Cited By
Double-network fracturing fluid thickening agent with high salt resistance and shear resistance and preparation method thereof
CN121362294A